Habituasi sebagai Strategi Pembentukan Karakter dalam Pengelolaan Lingkungan Berbasis KALINGGA di SMPN 39 Semarang - Laela Kurnia Nafitasari; Fajar Fajar (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
Character formation in environmental management requires a structured and sustainable habituation mechanism embedded in students daily school practices. This study aims to analyze habituation as a strategic mechanism for character formation in KALINGGA based environmental management atSMP Negeri 39 Semarang. The study employed a descriptive qualitative approach involving KALINGGA advisors as key informants, KALINGGA members as primary informants, and non-KALINGGA students as supporting informants. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal that KALINGGA based environmental pratices through five operational divisions, including innovation, waste management, water and energy conservation, and tree maintenance. Through continuous interaction supported by cultural, social, and symbolic capital, these repeated practices gradually develop into an environmental habitus among students. The study concludes that environmentally resposible character is formed not only through cognitive understanding, but through the integration of habituation, capital, and social arena within everyday school environmental management